Short-term pharmacologic RAGE inhibition differentially affects bone and skeletal muscle in middle-aged mice - Davis, Hannah M.; Essex, Alyson L.; Valdez, Sinai; Deosthale, Padmini J.; Aref, Mohammad W.; Allen, Matthew R.; Bonetto, Andrea; Plotkin, Lilian I. (Bone (New York, N.Y.), 2019)
Loss of bone and muscle mass are two major clinical complications among the growing list of chronic diseases that primarily affect elderly individuals. Persistent low-grade inflammation, one of the major drivers of aging, is also associated with both bone and muscle dysfunction in aging. Particularly, chronic activation of the receptor for advanced glycation end products (RAGE) and elevated levels of its ligands high mobility group box 1 (HMGB1), AGEs, S100 proteins and Aβ fibrils have been linked to bone and muscle loss in various pathologies. Further, genetic or pharmacologic RAGE inhibition has been shown to preserve both bone and muscle mass. However, whether short-term pharmacologic RAGE inhibition can prevent early bone and muscle loss in aging is unknown. To address this question, we treated young (4-mo) and middle-aged (15-mo) C57BL/6 female mice with vehicle or Azeliragon, a small-molecule RAGE inhibitor initially developed to treat Alzheimer's disease. Azeliragon did not prevent the aging-induced alterations in bone geometry or mechanics, likely due to its differential effects [direct vs. indirect] on bone cell viability/function. On the other hand, Azeliragon attenuated the aging-related body composition changes [fat and lean mass] and reversed the skeletal muscle alterations induced with aging. Interestingly, while Azeliragon induced similar metabolic changes in bone and skeletal muscle, aging differentially altered the expression of genes associated with glucose uptake/metabolism in these two tissues, highlighting a potential explanation for the differential effects of Azeliragon on bone and skeletal muscle in middle-aged mice. Overall, our findings suggest that while short-term pharmacologic RAGE inhibition did not protect against early aging-induced bone alterations, it prevented against the early effects of aging in skeletal muscle. •Short-term RAGE inhibition with Azeliragon (AZ) attenuated the aging-related body composition changes in fat and lean mass.•AZ administration reversed the skeletal muscle alterations induced in early aging.•AZ did not prevent the aging-induced bone alterations, likely due to its differential effects on bone cell viability/function.•Aging differentially altered glut transporter and metabolic enzyme expression in bone and skeletal muscle.•AZ treatment had differential effects on bone and skeletal muscle in middle-aged mice.